Effects of quinoa on cardiovascular disease and diabetes: a review - Zhang, He; Li, Ruiqi (Frontiers in Nutrition, 2024)
Quinoa is an annual dicotyledonous plant of Chenopodiaceae. As a functional healthy food with outstanding nutritional value, quinoa not only has a balanced proportion of amino acids, but also has higher contents of protein, unsaturated fatty acids, vitamins and minerals (K, P, Mg, Ca, Zn, Fe) than most cereal crops. Quinoa is also rich in active ingredients, such as polyphenols, flavonoids, saponins, polysaccharides, peptides, ecdysone, which can offer balanced nutrition, enhance the body function, regulate blood sugar, decrease blood lipid, increase anti-oxidation and anti-inflammatory action, prevent and treat cardiovascular diseases. Thus, quinoa is especially suitable for people suffering from chronic diseases, such as diabetes, hypertension, hyperlipidemia and heart disease and the elderly people to eat. Because of its comprehensive nutritional value and edible functional characteristics, quinoa is better than most grains, and has become a full nutritional food suitable for human consumption. This article reviews the active ingredients and physiological functions of quinoa, aiming to provide reference for further research and its utilization in food and drugs, food health care and pharmaceutical research and development.